2020
DOI: 10.1002/srin.202000439
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution during Homogenization and Hot Deformation for As‐Cast H13 Steel

Abstract: The hot compression experiments are accomplished to investigate the microstructural evolution of as‐cast H13 steel during homogenization treatment and hot deformation. At a certain homogenization temperature, the dynamic recrystallization (DRX) volume fraction increases with increasing strain and deformation temperature and decreasing strain rate. However, the DRX is also easy to proceed at a high strain rate of 5 s−1 due to the high shear stress. The recrystallization is inhibited in a dendrite segregation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…At 420 °C, which was close to the Bs temperature, the bainitic driving force further decreased. In the early stages of the transformation, it was accepted that the grain boundary is a fast channel for element diffusion; [ 31 ] therefore, only a small fraction of acicular bainite was formed at the prior austenite grain boundaries (PAGBs). Because the carbon in bainite had no time to diffuse, it precipitated in the form of carbides.…”
Section: Discussionmentioning
confidence: 99%
“…At 420 °C, which was close to the Bs temperature, the bainitic driving force further decreased. In the early stages of the transformation, it was accepted that the grain boundary is a fast channel for element diffusion; [ 31 ] therefore, only a small fraction of acicular bainite was formed at the prior austenite grain boundaries (PAGBs). Because the carbon in bainite had no time to diffuse, it precipitated in the form of carbides.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al [ 34 ] found that a higher strain rate promotes DRX kinetics at elevated temperatures. Han et al [ 35 ] suggested that it is easier to obtain small equiaxed grains at high strain rates than at low strain rates. Hodgson et al [ 36 ] proposed a model that describes the effects of strain, strain rate, and temperature on the recrystallization fraction, as follows{ X=1exp(0.693(tt0.5)n)t0.5=Aε−md0pZqexp(Qrex RT)Z=trueε˙exp(QdefRT) $$\left{\right.…”
Section: Discussionmentioning
confidence: 99%
“…When the homogenisation temperature was higher than Ac 3 , the crystal structure of experimental steel was γ -Fe. A temperature of 1200°C was selected as the homogenisation temperature of the γ -Fe phase region [16]. Homogenisation processes were carried out in a chamber electric furnace.…”
Section: Methodsmentioning
confidence: 99%